68.0k views
0 votes
What is the simplified form of (x – 2)(2x +3)? Use the Distributive Property.

2x2 – x – 6
2x2 – 6
2x2 – 7x – 6
2x2 + x – 6
2. What is the simplified form of (3x + 2)(4x – 3)? Use a table.
12x2 + 18x + 6
12x2 + x – 6
12x2 + 18x – 6
12x2 – x – 6
3. What is the simplified form of (4p – 2)(p – 4)?
4p2 + 6p – 16
4p2 – 18p + 8
4p2 – 14p – 6
4p2 – 6p + 16
4. The radius of a cylinder is 3x – 2 cm. The height of the cylinder is x + 3 cm. What is the surface area of the cylinder? Use the formula A = 2r2 + 2rh.

User Poik
by
4.9k points

2 Answers

4 votes

Answer:

Algebra 1 B | Unit 3: Polynomials and Factoring

Lesson 3: Multiplying Binomials quick check answers

Explanation:

1. A, 2x^2 - x - 6

2. D, 12x^2 - x - 6

3. B, 4p^2 - 18p + 8

4. D, 2pi(12x^2 - 5x - 2)

5. C, 6x^3 + 14x^2 - 5x - 3

User Davydotcom
by
4.6k points
3 votes

1. What is the simplified form of (x – 2)(2x +3)? Use the Distributive Property.

= (x)(2x) + (3)(x) - (2)(2x) - (2)(3)

= 2x^2 + 3x - 4x - 6

= 2x^2 - x - 6

Answer

2x^2 - x – 6

2. What is the simplified form of (3x + 2)(4x – 3)? Use a table.

| 3x 2

--------|-----------------------------------------

4x | 12x^2 8x

--------|---------------------------------------------

-3 | -9x -6

---------------------------------------------------------Add

12x^2 + 8x - 9x - 6

= 12x^2 -x - 6

Answer

12x^2 – x – 6

3. What is the simplified form of (4p – 2)(p – 4)?

(4p – 2)(p – 4)

= (4p)(p) - (4p)(4) - (2)(p) - (2)(-4)

=4p^2 - 16p - 2p + 8

= 4p^2 - 18p + 8

Answer

4p^2 – 18p + 8

4. The radius of a cylinder is 3x – 2 cm. The height of the cylinder is x + 3 cm. What is the surface area of the cylinder? Use the formula A = 2r2 + 2rh.

A = 2r2 + 2rh

A = 2( 3x – 2)^2 + 2 (3x – 2)(x + 3 )

A = 2(9x^2 - 12x + 4) + 2(3x^2 + 7x - 6)

A = 18x^2 - 24x + 8 + 6x^2 + 14x - 12

A = 24x^2 - 10x - 4

Answer

A = 24x^2 - 10x - 4

User Phil Mander
by
4.3k points